O caminho das flores: estudo econológico sobre a "Escola de Artes do Rio das Mortes" eo modelo intencional de encomenda - Minas Gerais (c. 1785-c.1841) - Kellen Cristina Silva (2018)
Based on the spatial mobility of the painter Joaquim José da Natividade, this work aims to present a panorama of the pictorial art produced in the region of Rio das Mortes County, Minas Gerais, at the turn of the 18th century to the 19th century, taking into account the role of the image for this nineteenth century society, the social place occupied by the painters, the teaching and learning in the workshops, the action of the brotherhoods as sponsors of artistic works, as well as highlighting iconographic aspects of the images produced. I raise the hypothesis of the existence of an "art school" in the region of Rio das Mortes County, where I believe that the painters Manuel Victor de Jesus, Venâncio José do Espírito Santo and Joaquim José da Natividade have been interacting, exponents of what I call "Visual Culture of Rio das Mortes". Through the trajectory of Natividade, an artist who has in the flowers produced one of his main manner, I try to understand how the dynamics of miscigenation contributed to the rise of talented crossbreeds to military positions. I also analyze the iconography produced in the region, taking into account the Intentional Model of Order, which allowed the representation of religious images with the most varied social aspects. The hypothesis defended here is that the crossbreed artists reached distinct places in nineteenth-century Minas Gerais society by recognizing their talent in performing the most varied paintings. Linked to this hypothesis, we have the possibility of teaching and learning of art, which contributed to the emergence of regional styles, such as the "arts school" of Rio das Mortes, the focus of this research. I try to demonstrate throughout the thesis the social relations that permeated the whole process of realizing the artistic order, in this case, the image produced in the form of painting.